Stem cell factor’s role in enhancing the quality of fertilized and cloned porcine embryos for improved embryonic stem cell derivation - Cai, Lian; Hyun, Sang-Hwan; Kim, Eunhye (Frontiers in Veterinary Science, 2023)
Stem cell factor (SCF), a cytokine growth factor, is expressed in various tissues of the male and female reproductive organs, including the testis, ovary, and endometrium. Its primary function involves cell survival, differentiation, and proliferation, achieved through its binding to the c-kit receptor. This study aimed to scrutinize the effects of SCF treatment during in vitro culture (IVC) on both the developmental potential and the efficiency of establishing embryonic stem cells (ESCs) from fertilized and cloned porcine embryos. The rates of cleavage and blastocyst formation exhibited no significant differences between fertilized and cloned embryos, even with the addition of SCF. However, it's worth noting that embryos cloned with Jeju #3-SBone-Dppb-pigTYR-CreERT2 (Braf) as donor cells demonstrated notably increased rates of hatched blastocysts when treated with SCF, and this increase was statistically significant (P < 0.05). Furthermore, following the complete dissection of the blastocysts, although there was no significant difference in the SCF-treated group, the area of expansion was significantly reduced (P < 0.01) in the group treated with the antagonistic blocker (ACK2) compared to both the control and SCF-treated groups. These outcomes suggest that the SCF/c-kit signaling pathway might play a pivotal role in embryo implantation. As anticipated, the efficiency of deriving ESCs was significantly higher (P < 0.01) in the group subjected to SCF treatment (12.82 ± 1.02%) compared to the control group (5.41 ± 2.25%). In conclusion, this study highlights the crucial role of SCF in enhancing the quality of porcine embryos, a vital step in obtaining high-quality ESCs.